Effects of a polyphenol present in olive oil, oleuropein aglycone, in a murine model of intestinal ischemia/reperfusion injury. Issue 2 (1st February 2013) - Campolo, Michela; Di Paola, Rosanna; Impellizzeri, Daniela; Crupi, Rosalia; Morittu, Valeria Maria; Procopio, Antonio; Perri, Enzo; Britti, Domenico; Peli, Angelo; Esposito, Emanuela; Cuzzocrea, Salvatore
Abstract : Oleuropein aglycone reduces damage in SAO‐shocked mice. Abstract : Dietary olive oil supplementation and more recently, olive oil phenols have been recommended as important therapeutic interventions in preventive medicine. Ole has several pharmacological properties, including antioxidant, anti‐inflammatory, antiatherogenic, anticancer, antimicrobial, and antiviral and for these reasons, is becoming an important subject of study in recent years. The aim of this study was to investigate the effects of Ole aglycone on the modulation of the secondary events in mice subjected to intestinal IRI. This was induced in mice by clamping the superior mesenteric artery and the celiac trunk for 30 min, followed by release of the clamp, allowing reperfusion for 1 h. After 60 min of reperfusion, animals were killed for histological examination of the ileum tissue and immunohistochemical localization of proinflammatory cytokines (TNF‐α and IL‐1β) and adhesion molecules (ICAM‐1 and P‐sel); moreover, by Western blot analysis, we investigated the activation of NF‐κB and IκBα. In addition, we evaluated the apoptosis process, as shown by TUNEL staining and Bax/Bcl‐2 expressions. The results obtained by the histological and molecular examinations showed in Ole aglycone‐treated mice, a decrease of inflammation and apoptosis pathway versus SAO‐shocked mice. In conclusion, we propose that the olive oil compounds, in particular, the Ole aglycone, could represent a possible treatment against secondary events of intestinal IRI.